Parametric Cox’s Model for partly interval-censored data with application to AIDS studies - Elfaki, Faiz Ahmed Mohamed; Azram, Mohammad; Usman, Mustofa (International Association of Computer Science and Information Technology Press (IACSIT), 2012)
The Parametric Cox’s Proportional Hazard Model based on Expectation-Maximization (EM) algorithm for partly interval-censored data is studied. We mean by partly interval-censored data that the observed data include both the exact and interval-censored observations on the survival time of interest. Through the simulation data and real data, we demonstrate that the resulting estimate of regression coefficient and its associated standard error. Our proposal is easily implemented by using SAS software in the present of partly interval-censored data.